2014
DOI: 10.1007/s12663-013-0614-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intra Ocular Pressure in Zygomatico Maxillary Complex Fractures

Abstract: Purpose To study effects of zygomatico maxillary fractures and fracture reduction on intra ocular pressure (IOP). Materials and methods IOPs of 20 patients with unilateral zygomatico-maxillary complex (ZMC) fractures (divided into 2 groups of 10 undisplaced, 10 displaced) were measured at various time intervals. The relationship between IOPs between the two groups at various time intervals was recorded and evaluated using independent T-tests. Results 20 subjects were divided into two equal groups (10 each of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…In our study pre-operatively there was elevated Intraocular Pressure of affected eye, which could be due to pre-operative subconjuctival hemorrhage, retrobulbar hemorrhage, circumorbital edema and ecchymosis and diplopia. Kuye OF et al 2020 [18] and Sharma R et al (2015 [9] also obtained the same results. According to Dongmei H at al 2007 [19] when anatomy of orbit is disrupted, soft tissue of the orbit can herniate into the displaced fragments, creating a trapdoor like effect.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In our study pre-operatively there was elevated Intraocular Pressure of affected eye, which could be due to pre-operative subconjuctival hemorrhage, retrobulbar hemorrhage, circumorbital edema and ecchymosis and diplopia. Kuye OF et al 2020 [18] and Sharma R et al (2015 [9] also obtained the same results. According to Dongmei H at al 2007 [19] when anatomy of orbit is disrupted, soft tissue of the orbit can herniate into the displaced fragments, creating a trapdoor like effect.…”
Section: Discussionsupporting
confidence: 52%
“…elevation in intraocular pressure may be due to stimulation of the central ends of the vagus nerve which cause the release of substances that elevate blood pressure. Sharma R et al 2015 [9] also observed similar results.Then the signi cant decrease in IOP was observed in both the groups between 24 hours to 7 days post-surgery. Sharma R et al 2015 [9] and Paton et al 2006 [20] also reported the similar trend of IOP in their studies.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Exposure keratitis was also seen in one ZMC case. In the cases taken up for open reduction and internal fixation of ZMC fractures, there was no statistically significant difference between the heart rate pre-operatively and at the time of reduction of the fracture, indicating that was no significant change in the heart rate (bradycardia secondary to oculocardiac reflex during reduction of ZMC fractures) which is due to the anesthetic agents and the local infiltration of adrenaline that is given [29].…”
Section: Discussionmentioning
confidence: 95%
“…[ 2 14 ] Eliciting the relevant signs and symptoms is usually important as they can be pointers in the diagnosis of ophthalmic injuries, most especially in patients who are unconscious and unable to describe their symptoms. [ 15 ] It is important to note that some ophthalmic injuries may not be apparent, and potentially blinding complications may easily be missed unless actively sought for. [ 2 7 ] On the other hand, inadequate care can result in blindness, with its attendant social and medico-legal implications.…”
Section: Introductionmentioning
confidence: 99%